Performance of cooperative diversity aided TF-spread MC-DS-CDMA with preprocessing. (September 2019) - N, Prabagarane; AL-HILFI, Haider Mohammed Turki; M, Tamilarasi
Highlights: A single RS supporting all the K DL users' DMSs. When each DMS is supported by one relay. Each DMS is supported by a cluster of L RSs. Abstract: This correspondence investigates cooperative diversity assisted downlink multi-carrier communications, by invoking three cooperation policies. In this contribution, multi-user interference (MUI) at the relay stations (RSs) and inter-relay interference (IRI) at the destination mobile stations (DMSs) are mitigated with the aid of preprocessing operated at the base station (BS) and RSs, respectively. Specifically, the BS employs an orthogonal subspace based preprocessing approach and that each of the RSs use transmitter zero-forcing to combat interference. Our simulation study demonstrates that preprocessing efficiently suppresses the MUI at the RSs and IRI at the DMSs, thus aiding in enhancing diversity gain that contributes to performance improvement of the system. Graphical abstract: Image, graphical abstract